Miras as a distance indicator in the CSST, JWST, and Gaia era - Sun, Yan; Zhang, Jingdong; Zhang, Bo; Xu, Shuangjing; Mai, Xiaofeng; Ding, Hao; Chen, Wen; Wen, Shiming (Frontiers in Astronomy and Space Sciences, 2023)
Mira variables are important distance indicators owing to the clear period–luminosity relation at infrared wavelengths. We have compiled a sample of 343 Galactic Miras selected from the American Association of Variable Star Observers database and Gaia Data Release 3. We used V-band observations from the American Association of Variable Star Observers to generate template light curves and derived mean magnitudes in the near-infrared JHK band from the Two Micron All-Sky Survey. Based on the Gaia-Two Micron All-Sky Survey diagram and the Gaia-LPV2 catalog, we classified 299 O-rich and 44 C-rich Miras. We fitted the Galactic period–luminosity relations for O-rich Miras in the near-infrared JHK band and estimated slopes (–2.74 ± 0.32, –3.14 ± 0.30, and –3.50 ± 0.25) and zero points (–5.58 ± 0.06 mag, –6.40 ± 0.06 mag, and –6.84 ± 0.05 mag) defined at logP (days) = 2.30, separately. Although the uncertainties of our derived Galactic PLRs for Miras are still larger than those of other galaxies, the multi-band sky survey conducted using the China Space Survey Telescope could help build more reliable and accurate PLRs for Miras, particularly in a near-infrared y band (927–1,080 nm).